Analisis Kerja Sama Malacca Straits Patrol, 2005-2009 - Rahmadanu Pradityo (Yogyakarta State University, 2021)
The Malacca Strait is one of the busiest straits in the world because it is an important route for international trade connecting western Asia with eastern Asia. The high traffic of ships in the Malacca Strait poses a separate threat to maritime security as it is a target area for ship hijacking and armed robbery. Therefore, the coastal countries around the Malacca Strait must respond to these threats unilaterally, bilaterally, and multilaterally. One of the responses of littoral states around the Strait of Malacca by conducting coordinated patrols (Malacca Straits Patrol). This paper analyzes this cooperation using a maritime security matrix.